Effect of Forms of Pharmaceutical Preparations on Antibacterial Activity of Red Betel Oil (Piper crocatum Ruiz & Pav.) - Marchaban Marchaban; Anisa Ragil Handayani; Elsa Putri Kartika; Sudarsono Sudarsono (Majalah Farmaseutik, 2019)
The Red Sirih Essential Oil (RSEO) which be obtained from red betel leaf (Piper crocatum Ruiz & Pav.) by water and vapour distillation has potential as antibacterial activity. Formulation of an active pharmaceutical ingredient to become a pharmaceutical dosage form can generally modify their activity. The aim of the study is to proof the influence of dosage forms to the activity of RSEO. The study was done by formulating the RSEO to become emulsion, microemulsion and solubilisation dosage forms, and then, their antibacterial activity againt Escherichia coli ATCC 25922 by microdilution method of 1.25% using ELISA reader at 570 nm. The results showed that formulation reduced antibacterial activity. The raw RSEO had a Bacterial Growth Inhibition (BGI) of 66.59%, whereas microemulsion had 49.58%, emulsion had 17.45%, and solubilisation had 0% of BGI, that mean lost its antibacterial activity.